Control of Obesity, Blood Glucose, and Blood Lipid with Olax imbricata Roxb. Root Extract in High-Fat Diet-Induced Obese Mice - Thi Nga Vo; Thi-Diem-My Luong; Thi-Phuong-Hoa Le; Khanh Son Trinh (Journal of Toxicology)
Mice were used in in vivo experiments to evaluate the effects of doses of n-hexane extract (from 100 to 1,300 mg/kg body weight/day) on the ability to control obesity, blood glucose, and blood lipid. In this study, body weight gain, caloric intake, glucose tolerance, blood lipid, histopathological study, and locomotion activity were examined. Furthermore, this study evaluated the lethality of the extract in extremely high doses in the tested mice. After 3 months of use with an extremely high dose of 5,000 mg/kg body weight/day (equivalent to 350 g/day for a 70 kg person), no animals with abnormal conditions or death were observed. This initially demonstrated the safety of the extract. In addition, after 6 weeks of testing on high-fat diet-induced obese mice, n-hexane extract at a dose of 500 mg/kg body weight/day (equivalent to 35 g/day for a 70 kg person) demonstrated a positive effect on the ability to control obesity, blood glucose, and blood lipid through the results of body weight, blood lipids, glucose tolerance, and histopathology (white fat, liver, and kidney tissues). In this study, n-hexane extract from the roots of Duong-dau tree has proven to be strongly biologically active in preventing and supporting the treatment of diseases related to overweight and obesity, helping to control blood glucose levels thereby reducing the risk of type 2 diabetes.